Trust as a factor activating implementation abilities - from theory to practice of a flexible company = Zaufanie jako czynnik aktywizujący zdolności implementacyjne - od teorii do praktyki elastycznego przedsiębiorstwa - Nogalski, Bogdan; Niewiadomski, Przemysław (Zielona Góra: Faculty of Economics and Management Press)
As a result of the wide recognition of the importance of trust as an element related to the cooperation in a variable and hardly predictable environment, the trust was appreciated by management sciences. Thanks to the trust, the organisation can react quickly to changes in a complex and turbulent environment, in which it is necessary to develop new - adequate to the needs - products. In the context of the above, the research was commenced, whose execution was the condition of an attempt to answer the question: is the number of the products implemented by the manufacturer a derivative of trust built between him/her and his/her recipients?
Keywords: zaufanie; implementacje bazujące na zaufaniu; elastyczność implementacyjna; trust; implementations based on trust; implementation flexibility